Baby words - Butterfield, Moira (Ladybird, 1995)
Based on the belief that babies love looking at other babies, this book depicts early words and noises, such as boo, peepo, mine, no. These words are introduced in context through situations they may recognize. The boards are non-toxic and CE tested.